The Influence of Motivation on EFL Learners’ Speaking Skills (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Motivation is one of some psychological factors which influences the speaking proficiency. Therefore, this study aims at finding out whether or not there is a significant correlation between EFL learners’ motivation and their speaking skills. With regard to the methodology applied in this study, a correlation research was used to determine whether, and to what degree, a relationship exists between two or more quantifiable variables in form of quantitative method. Purposive sampling was used in the correlational research due to the assumption that the selected students were able to give information or data in relation to the research problems based on the research design. Thus, 46 learners were chosen as the samples. The study was conducted at learners in SMA Negeri 1 Marisa, Pohuwato Regency, Gorontalo. Moreover, the quantifiable data were obtained from speaking test based on the Heaton assessment and motivation test based on the Likert Scale assessment which were distributed to the learners. The data were then analyzed by Pearson product moment. The findings showed that there was a significant correlation between EFL learners’ motivation and their speaking skills in degree of high correlation. In other words, the assumption views that that the higher motivation belongs to EFL Learners to speak the better ability they speak.
Keywords: Motivation; Speaking Skills; EFL learners